The Effect of Labor-Saving Devices Upon Wages - Johnson, Alvin S. (Quarterly Journal of Economics, 1905)
Journal Article The Effect of Labor-Saving Devices upon Wages Get access Alvin S. Johnson Alvin S. Johnson Columbia University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 20, Issue 1, November 1905, Pages 86–109, https://doi.org/10.2307/1882556 Published: 01 November 1905